Microbiological Profile of Peritoneal Dialysis-Related Peritonitis at Dr. Hasan Sadikin Hospital, Bandung - Dania Artriana; Llik Sukesi; Rizky Andhika (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Background: Peritonitis is a frequent complication in patients undergoing peritoneal dialysis. To provide appropriate therapy, identification of the pathogen that causes peritonitis is required. Objective: This study aims to understand the microbiological profile of CAPD peritonitis in hospitalized patients at Dr. Hasan Sadikin Hospital, Bandung. Methods: This was a descriptive retrospective study using secondary data of peritonitis patients undergoing CAPD in 2020-2023. A total sampling technique was used, where all cases that met the inclusion criteria were included. The criteria were patients aged ≥ 18 years with CAPD peritonitis, having complete medical record data, and CAPD fluid culture results. In addition, the data were analyzed using SPSS software. Results: A total of 67 peritonitis patients undergoing CAPD were included, with 36 (53.7%) having monomicrobial infections. In addition, 7.5% had polymicrobial infection and 38% had culture-negative. Gram-negative bacteria were the most common microbe found in 18 cases, and most patients recovered from peritonitis (86.6%), followed by catheter removal (9%), and death (4.5%). Gram-negative predominance contrasts with Ozdemir et al.’s findings, possibly due to regional antibiotic practices. Conclusion: Empirical antibiotic treatment and culture results helped in providing effective management. Adhering to ISPD guidelines and improving sampling techniques could improve microbiological diagnosis and patient outcomes.